2014
DOI: 10.2478/jas-2014-0025
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Bee Colonies Headed by Queens Instrumentally Inseminated with Semen of Drones Who Come from a Single Colony or Many Colonies

Abstract: A b s t r a c t The aim of the study was to determine the effect of honey bee worker diversity within the colony on: development, honey productivity, and wintering. Two different levels of diversity within the colony were tested. The appropriate levels of diversity within the colony were obtained by selecting drones for inseminating the queens. Lower genetic diversity was obtained in the colonies headed by a queen inseminated with semen collected from drones originating from a single colony. Higher genetic div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…When inseminating queens instrumentally, breeders can mimic the situation on mating stations; i.e., use the sperm of drones from a sister group of drone-producing colonies to fertilize the queens [ 5 , 7 ]. But a wide range of alternative procedures is possible, reaching from the use of mixed semen from large numbers of drones [ 90 ] to inseminations with drones from a single colony [ 91 ] or even single-drone inseminations [ 92 ]. In his simulation studies, Moritz [ 46 ] propagated artificial insemination with mixed sperm of many drones.…”
Section: Discussionmentioning
confidence: 99%
“…When inseminating queens instrumentally, breeders can mimic the situation on mating stations; i.e., use the sperm of drones from a sister group of drone-producing colonies to fertilize the queens [ 5 , 7 ]. But a wide range of alternative procedures is possible, reaching from the use of mixed semen from large numbers of drones [ 90 ] to inseminations with drones from a single colony [ 91 ] or even single-drone inseminations [ 92 ]. In his simulation studies, Moritz [ 46 ] propagated artificial insemination with mixed sperm of many drones.…”
Section: Discussionmentioning
confidence: 99%
“…However, Harbo (1990) found that a careful stirring of the 1:1 semen diluent, worked as well as centrifugation. The hand-stirring method has been used in different studies (Skowronek et al 1995;Gerula et al 2014). Usually drone semen is not diluted, unless necessary for research.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many factors strongly impact the success of insemination, including total asepsis, mucus presence in the syringe and time needed to complete the insemination [ 23 , 54 , 55 ]. The losses in our study could also be linked to a genetic weakness within the colony caused by the insemination of queens by related drones [ 56 , 57 , 58 , 59 ]. Low genetic diversity within a colony reduces the behavioral diversity of the workers and limits population growth, with repercussions on the use of environmental resources and even on resistance to diseases, parasites and environmental fluctuations [ 3 , 56 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 95%